2011
DOI: 10.1103/physreve.83.011103
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stability of quantum chaotic ratchets

Abstract: The transitory and stationary behavior of a quantum chaotic ratchet consisting of a biharmonic potential under the effect of different drivings in contact with a thermal environment is studied. For weak forcing and finiteh, we identify a strong dependence of the current on the structure of the chaotic region. Moreover, we have determined the robustness of the current against thermal fluctuations in the very weak coupling regime. In the case of strong forcing, the current is determined by the shape of a chaotic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Examples of ratchet models (as they are also usually referred to) have found application in many areas of research. Here we will mention just a few, such as biology [4], nanotechnology [5], granular crystals [6], and some chemical reactions as isomerization [7]. This gives an idea of how different the fields of interest could be.…”
mentioning
confidence: 99%
“…Examples of ratchet models (as they are also usually referred to) have found application in many areas of research. Here we will mention just a few, such as biology [4], nanotechnology [5], granular crystals [6], and some chemical reactions as isomerization [7]. This gives an idea of how different the fields of interest could be.…”
mentioning
confidence: 99%
“…We have studied two paradigmatic systems, namely the DMKRM [14], and a generic, continuously driven DPDDS [15] We have found that we can always identify a classical chaotic attractor which corresponds to the quantum one. In general, there are no paradoxes in the quantum to classical correspondence of dissipative systems when we add Gaussian fluctuations to the classical counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…This system is interesting to simulate a molecule with two stable isomers that is under the influence of a monochromatic laser field pulse, for which the term sin(x) represents the dipole coupling [15]. But it is also of general nature, and the results obtained through its study can be directly applied to many different situations, including for example many body systems [9].…”
Section: B Dpddsmentioning
confidence: 99%
See 2 more Smart Citations